Identifying How Patient Portals Impact Communication in Oncology. Issue 12 (15th October 2019) - Alpert, Jordan M.; Morris, Bonny B.; Thomson, Maria D.; Matin, Khalid; Brown, Richard F.
ABSTRACT: Patient portals are becoming widespread throughout health-care systems. Initial research has demonstrated that they positively impact patient–provider communication and patients' health knowledge, but little is known about the impact of patient portals in the cancer setting, where highly complex and uncertain medical data are available for patients to view. To better understand communicative behaviors and perceptions of the patient portal and how it is utilized in oncology, in-depth, semi-structured interviews were conducted with 48 participants: 35 patients and 13 oncologists. Thematic analysis identified that portals help to enhance participation during in-person consultations, increase patients' self-advocacy, and build rapport with providers. However, patients' comfort level with reviewing information via the portal depended upon the severity of the test. Oncologists worried about patient anxiety and widening health disparities, but acknowledged that the portal can motivate them to expedite communication about laboratory and scan results. As patient portals become more widely used in all medical settings, oncologists should become more engaged with how patients are viewing their medical information and consider the portal within the framework of patient-centered care by valuing patients' communication preferences.